Optimized Regional Development Planning for Samosir Tourism: Integrating Seasonal Accommodation Occupancy and Sustainable MSME Empowerment - Dina Rosari; Ngatemin Ngatemin; Dewi Yanti; Bejo Mulyadi (LPPM Universitas PGRI Sumatera Barat, 2026)
This study examines tourism seasonality's impact on accommodation occupancy and MSME performance in Samosir Regency, Lake Toba UNESCO Global Geopark, using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with a complete census of 80 stakeholders. Results confirm seasonality strongly predicts occupancy fluctuations (β=0.69, p<0.001, R²=0.48), while bidirectional occupancy-MSME linkages explain 41% of MSME revenue instability (β=0.46/0.31, p<0.001/0.002). Stakeholder integration emerges as the dominant driver of regional planning effectiveness (β=0.51, p<0.001), alongside occupancy (β=0.24) and MSME inputs (β=0.33), accounting for 63% of planning variance (SRMR=0.067). Findings provide an empirical framework for optimized planning, integrating seasonality mitigation, MSME empowerment, and inclusive governance to achieve sustainable tourism development in Indonesia's super-priority destinations.